Adversity Quotient, Komitmen Kerja dan Kreativitas Guru SD Kelas satu - Weno, Julian H; Matulessy, Andik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
The purpose of this research was to determine the relationship between Adversity Quotientand Work Commitment to Creativity Teachers First Class in District Teluk Ambon,municipality of Ambon. Respondents in this study were 46 first classteacher in the district ofTeluk Ambon. There are three scales used in this study are: Scale of teaching creativity andcommitment to work using a Likert scale, while the scale of adversity quotient using Bogardusscale with numbers 1-5 choice. The results of multiple regression analysis found the value F= 17.811; R = 0.673; p = 0.000 (p <0.01), which proves that adversity quotient and workcommitment have a significant correlation with the creativity of teachers; no significantpositive correlation between adversity quotient withcreativity teachers, where t = -1.196; p =0.238 (p> 0.01); there is a Significant Positive correlation between work commitment withcreativity Teachers where the value t = 5.824; p = 0.000 (p <0.01).Keywords : Creativity Teachers, Adversity Quotient, Work Commitment, Teachers the firstClass.